2023
DOI: 10.1002/fft2.314
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy mechanisms research progress of the active components in the characteristic woody edible oils

Lili Xu,
Wei Wang,
Kaiwen Bai
et al.

Abstract: Woody edible oils are a type of vegetable oil. Woody edible oils like olive oil have greater quantities of unsaturated fatty acids (UFAs), particularly essential FAs, as well as vitamin E, phytosterols, and other nutrients that are becoming more vital in human health. As a result, finding high‐quality woody oil resource plants is critical to ensuring enough edible oil supply. As six novel woody crops, Paeonia suffruticosa, Plukenetia volubilis, Acer truncatum, Olea europaea, Camellia sinensis, and Camellia ole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 242 publications
0
1
0
Order By: Relevance
“…Guo et al (2020) from ethanol‐induced lipid accumulation mouse experiments found that Rosmarinic acid had a regulatory effect on ethanol‐induced inflammation by decreasing the levels of tumor necrosis factor‐α (TNF‐α). Xu et al (2023) found that supplementing with 400–800 IU of α‐Tocopherol per day could reduce the risk of cardiac arrest caused by coronary artery blockage and play a crucial role in preventing the development of atherosclerosis by inhibiting the accumulation of low‐density lipoprotein in blood vessels. This impact could potentially be facilitated by tocopherol's oxidative stress mechanism and its ability to reduce inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Guo et al (2020) from ethanol‐induced lipid accumulation mouse experiments found that Rosmarinic acid had a regulatory effect on ethanol‐induced inflammation by decreasing the levels of tumor necrosis factor‐α (TNF‐α). Xu et al (2023) found that supplementing with 400–800 IU of α‐Tocopherol per day could reduce the risk of cardiac arrest caused by coronary artery blockage and play a crucial role in preventing the development of atherosclerosis by inhibiting the accumulation of low‐density lipoprotein in blood vessels. This impact could potentially be facilitated by tocopherol's oxidative stress mechanism and its ability to reduce inflammation.…”
Section: Resultsmentioning
confidence: 99%